Conducting polymer micro-supercapacitors for flexible energy storage and Ac line-filtering. (April 2015) - Kurra, Narendra; Hota, M.K.; Alshareef, H.N.
Abstract: We propose a novel surfactant-mediated process to fabricate flexible microsupercapacitors (MSCs) combining conventional photolithography and electrochemical deposition. The anionic surfactant mediates the process of electropolymerisation at a lower anodic potential while causing template effects in producing porous conducting poly(3, 4-ethylenedioxythiophene) (PEDOT) electrodes. Using this strategy, PEDOT MSCs with remarkable performance in terms of tunable frequency response and energy density are achieved. Specifically, ultrahigh scan rate capability up to 500 V/s is achieved with a crossover frequency of 400 Hz at a phase angle of −45°. This is the first polymer-based redox microsupercapacitor with excellent frequency characteristics other than carbonaceous-based electrochemical double layer capacitors reported so far in the literature. Thus, the micro-supercapacitors exhibit maximum areal cell capacitance of 9 mF/cm 2 with a volumetric stack capacitance of 50 F/cm 3 in 1 M H2 SO4 aqueous electrolyte. The flexibility and stability of these PEDOT MSCs is tested in aqueous gel electrolyte which showed a capacitance retention up to 80% over 10, 000 cycles with a Coulombic efficiency of 100%. The maximum energy density of solid state ion gel based PEDOT MSCs was found to be 7.7 mW h/cm 3, which is comparable to the lithium based thin film batteries and superior to the current state-of-the-art carbon and metal oxide based MSCs. Further, the tandem configuration of flexible solid state ion gel based PEDOT MSCs is employed to demonstrate it as a power source for glowing a red light emitting diode. Graphical abstract: High energy density and ultrahigh rate capability of conducting polymer microsupercapacitors . Good Frequency Response and ultrahigh ratability obtained for conducting polymer microsupercapacitors. Surfactant mediated electrochemical deposition was used to fabricate polyethylenedioxythiophene microsupercapacitors with several excellent characteristics including frequency response and superior energy density over the current state-of-the-art carbon based microsupercapacitors. Highlights: This is the first conducting polymer-based redox microsupercapacitor with excellent frequency characteristics other than carbonaceous-based electrochemical double layer capacitors reported so far in the literature. The in-plane design, good electronic and ionic conductivity of PEDOT microsupercapacitors, , enabling high scan rate and power capabilities. The highly flexible nature of PEDOT microsupercapacitors with excellent cycling stability is demonstrated.